The monogamous/promiscuous optics in contemporary gay film: registering the amorous couple in Weekend (2011) and Paris 05:59: Théo & Hugo (2016). Issue 4 (1st October 2020) - Çakırlar, Cüneyt; Needham, Gary
ABSTRACT: This article explores representations of same-sex intimacy in contemporary gay cinema by focusing on two films, Weekend (2011) and Paris 05:59: Théo & Hugo (2016). Both films spatialise intimacy, which is reflected in a formal appeal to monogamous and promiscuous optics. What interests us here is how the relational politics of monogamy/promiscuity can be considered as stylistic and ideological registers in gay filmmaking. Informed by Leo Bersani's work, we investigate how gay cinema tests the social viability/intelligibility of same-sex intimacy against a centring of the self. Furthermore, we explore how gay films use form and style to situate both their politics and their spectators through spectacles of erotic relationality. Following Bersani, the article proposes a theory of cinematic optics that privilege the impersonal over the personal, and the ontological over the psychological. Weekend 'ovalises' intimacy and locates the couple formally and ideologically. The couple in Weekend 's space of sociality operates within a monogamous optic that presents intimacy through stabilising identities and psychologising subject positions. Théo & Hugo, however, reorients spectatorship as impersonal and promiscuous in finding a way to express the experience of cruising and sociability in ways that are dispersed and extensible.